Early response evaluation of PD-1 blockade in NSCLC patients through FDG-PET-CT and T cell profiling of tumor-draining lymph nodes. (31st December 2023) - Borm, Frank J.; Smit, Jasper; Bakker, Joyce; Wondergem, Maurits; Smit, Egbert F.; de Langen, Adrianus J.; de Gruijl, Tanja D.
ABSTRACT: Better biomarkers for programmed death - (ligand) 1 (PD-(L)1) checkpoint blockade in non-small cell lung cancer (NSCLC) are needed. We explored the predictive value of early response evaluation using Fluor-18-deoxyglucose positron emission tomography and pre- and on-treatment flowcytometric T-cell profiling in peripheral blood and tumor-draining lymph nodes (TDLN). The on-treatment evaluation was performed 7–14 days after the start of PD-1 blockade in NSCLC patients. These data were related to (pathological) tumor response, progression-free survival, and overall survival (OS). We found that increases in total lesion glycolysis (TLG) had a strong reverse correlation with OS ( r = −0.93, p  = 0.022). Additionally, responders showed decreased progressors and increased Treg frequencies on-treatment. Frequencies of detectable PD-1-expressing CD8 + T cells decreased in responders but remained stable in progressors. This was especially found in the TDLN. Changes in activated Treg rates in TDLN were strongly but, due to low numbers of data points, non-significantly correlated with ΔTLG and reversely correlated with OS.